Obtrusiveness of smartphone applications for sleep health - M. Vazquez-Briseno; A. Laflor-Hernandez; Fernanda Murillo-Muñoz; Doreen Mendez-Verdugo (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Unobtrusiveness is one of the main issues concerning health-related systems. Many developers affirm that their systems do not burden users; however, this is not always achieved. This article evaluates the obtrusiveness of various systems developed to improve sleep quality. The systems analyzed are related to sleep hygiene, since it has become an interesting topic for researchers, physicians and people in general, mainly because it has become part of the methods used to estimate a persons’ health status A set of design elements are presented as keys to achieving unobtrusiveness. We propose a scale to measure the level of unobtrusiveness and use it to evaluate several systems, with a focus on smartphone applications.